2001
DOI: 10.1039/b103091b
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation and validation of a capillary electrophoresis method for the simultaneous determination of diazepam and otilonium bromide

Abstract: A simultaneous assay of diazepam and otilonium bromide in coated tablets by capillary zone electrophoresis (CZE) was developed. The influence of various parameters (voltage, temperature, buffer concentration and pH, ethanol percentage) on analysis time and on the theoretical plates of the two peaks was investigated by means of experimental design. A response surface study was carried out by means of a 27-run D-optimal matrix. The best background electrolyte was found to be 0.13 M, pH 2.9 Britton-Robinson buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Plackett-Burman design was used for the evaluation of robustness of three capillary zone electrophoresis methods [23,24,27] and an HPLC method [25]. In all cases, the ranges employed were small deviations from the method setting that would normally occur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plackett-Burman design was used for the evaluation of robustness of three capillary zone electrophoresis methods [23,24,27] and an HPLC method [25]. In all cases, the ranges employed were small deviations from the method setting that would normally occur.…”
Section: Resultsmentioning
confidence: 99%
“…As for the optimisation of method precision (repeatability), the Taguchi approach [12], the BoxMeyer approach [13], artificial neural networks [14] or experimental design methodology [15] are strategies that have been used. Further original applications of multivariate strategies to validation have dealt with evaluation of robustness [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31] and intermediate precision [21,25,26,32,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Codevilla et al (2012) developed and validated a capillary zone electrophoresis (CZE) method for determination of lodenafil carbonate in drug products. There are some advantages to use the CZE method, such as rapid analysis, small sample and reagent consumption, high separation efficiency (Furlanetto et al, 2001;Yang et al, 2010). The results obtained from the UV-spectrophotometric method and CZE method were compared statistically with the LC method (Codevilla et al, 2011a) and the results showed no significant difference between these methods.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…From the above results it clearly appears that the conditions required to optimize t are in conflict with the values needed to optimise R 1 . A simple way to resolve the problem is to use Derringer's desirability function (D) [14,15,19,29]. This function is a measure of overall quality and provides convenient means to compare several responses and to select the optimum with the most desirable properties.…”
Section: Microemulsion System Optimization By Mixture Designmentioning
confidence: 99%